Intraoral Photography Recommendations for Remote Risk Assessment and Monitoring of Oral Mucosal Lesions - Iris Lin; Madhurima Datta; Denise M. Laronde; Miriam P. Rosin; Bertrand Chan (Elsevier, 2021)
Oral cancer is a global health issue with substantial morbidity and a high mortality rate mainly because of late-stage diagnosis. Cancerous lesions are often preceded by potentially malignant lesions that may be detected during routine dental examinations. Not only is the oral cavity easily accessible for screening, but the clinical risk factors of the disease are also known. However, patients may not always be able to access screening services or receive follow-up for diagnosed lesions. In these circumstances, intraoral photos are crucial for timely triage, risk assessment, and monitoring of oral lesions. Further, photos form an integral part of a patient's records, facilitate patient education and communication between health care providers, and provide important information during the referral process. To ensure that intraoral photos are of good quality and standardised there is a need to establish recommendations regarding intraoral photography in oral mucosal screening. This article recommends methods to help health professionals and patients obtain interpretable intraoral photographs. Suggestions to achieve ideal lighting, mirror placement, camera angle, and retraction have been discussed. These recommendations are adaptable to easily available smartphone or point-and-shoot cameras and may be further used to develop future teledentistry platforms.